Metal-stabilized carbocations derived from monoterpenes: dicobalt hexacarbonyl complexes of alkynyl-verbenols. Issue 29 (21st July 2016) - Moore, Angela; Ostermann, Johannes; Müller-Bunz, Helge; Ortin, Yannick; McGlinchey, Michael J.
Abstract: Nucleophilic attack by alkynyl anions on the verbenone skeleton occurs on the face opposite to that occupied by the gem -dimethyl group. The resulting alkynols react with dicobalt octacarbonyl to form tetrahedral (μ 2 -alkyne)Co2 (CO)6 clusters in which the tricarbonylcobalt moieties are diastereotopic, and treatment with dppm tags each of these vertices with a 31 P NMR label. Protonation yields a single cobalt-stabilized carbocation, 13a, in which the cobalt is situated on the side bearing the methylene bridge, thus avoiding the gem- dimethyl group, and pulls the capping phenyl substituent proximate to the hydrogen atom at C(3). All new molecules were characterized by NMR spectroscopy and by X-ray crystallography for syn -trimethylsilylethynylverbenol, 6, syn -ethynyl-verbenol, 7, and for the (2-phenylethynyl-4-methylene-6, 6-dimethyl-(1 S, 5 S )-bicyclo[3.1.1]hept-2-ene)Co2 (CO)4 (dppm) cluster, 12 . The 2-ethynyl-4-methylene-6, 6-dimethyl-bicyclo[3.1.1]hept-2-ene ligand, 15, was also prepared and characterized for the first time. Graphical abstract: